Short-Term and Highly Intensive Early Intervention FIAS: Two-Year Outcome Results and Factors of Influence - Herbrecht, Evelyn; Lazari, Olga; Notter, Marianne; Kievit, Esther; Schmeck, Klaus; Spiegel, René (Frontiers in Psychiatry, 2020)
Background: Comprehensive behaviourally or developmentally based early intervention programmes have been shown to be effective in improving cognitive, social communicative, and adaptive skills of children with autism spectrum disorder (ASD). Besides the definition of relevant outcome predictors, the question of whether early intensive intervention positively changes core autism symptoms in children, as well as their long-term outcome, is an important issue for current research. The primary objective of the current study was to examine whether symptomatic and behavioural changes in children up to 4.5 years with ASD were sustained one and two years after an initial 18 days of intensive FIAS (Frühintervention bei autistischen Störungen) intervention. Methods: We analysed the data of 32 young children with moderately severe to severe ASD who had been treated at the FIAS centre between January 2011 and July 2017 and who had completed their two-year follow-up in summer 2019. Results: ADOS total scores decreased significantly from baseline to the one-year follow-up and from baseline to the two-year follow-up (p<0.01), with the most prominent change being from baseline to two-year follow-up. The DD-C-GAS, a global scale used to assess four areas of everyday functioning, showed highly significant improvements on all subdomains. We found mostly significant correlations between results on both rating instruments at all time points, yet mostly no meaningful correlation between their changes over time. There was a close and statistically significant relationship between parents’ treatment adherence and ADOS scores, indicating that the better parents’ treatment adherence, the lower the children scored on the ADOS at one- and two-year follow-up. Overall, improvement on both scales was virtually independent of age and autism symptom severity at baseline, suggesting that older (> 43 months) and more severely affected children (ADOS total score > 20) may benefit from the FIAS intervention to the same extent as younger children do. Conclusions: The results of the study indicate that the FIAS approach of providing an initial highly intensive 18-day intervention period, followed by two years of less intensive follow-up care had an impact on the core autism symptoms as well as the adaptive functioning of children with ASD.